Role of Phosphodiesterase 4-Mediated Cyclic AMP Signaling in Pharmacotherapy for Substance Dependence - Wen, Rui-Ting; Feng, Wan-Yu; Liang, Jian-Hui; Zhang, Han-Ting (Current Pharmaceutical Design, 2015)
The harmful effects caused by misuse of psychoactive substances have raised both medical and social problems. Substance dependence is a chronic relapsing disorder, which appears to involve neuroadaptive changes in cellular signaling and downstream gene expression. The unchanged consumption of present substances and increasing demand for new psychostimulants make the development of novel management/treatment strategies challenging. Emerging evidence has shown that the cyclic AMP (cAMP) signaling cascade plays a critical role in the initiation and development of dependence. Thus, phosphodiesterase 4 (PDE4), the primary hydrolytic enzyme for intracellular cAMP, is considered a potential target for future therapeutics dealing with prevention and intervention of substance dependence. This implication is supported by recent data from preclinical studies, and the rapid development of PDE4 inhibitors. Taken together, specific inhibitors of PDE4 and its subtypes possibly represent a novel class of pharmacotherapies for the prevention and abstinence of substance dependence. Here we discuss the modulatory role of cAMP signal transduction in the process of substance dependence and highlight recent evidence that PDE4 inhibitors might be a promising approach to substance dependence therapy.
Keywords: cAMP